2022
DOI: 10.3390/nu14142846
|View full text |Cite
|
Sign up to set email alerts
|

Important Food Sources of Fructose-Containing Sugars and Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis of Controlled Trials

Abstract: Background: Fructose providing excess calories in the form of sugar sweetened beverages (SSBs) increases markers of non-alcoholic fatty liver disease (NAFLD). Whether this effect holds for other important food sources of fructose-containing sugars is unclear. To investigate the role of food source and energy, we conducted a systematic review and meta-analysis of controlled trials of the effect of fructose-containing sugars by food source at different levels of energy control on non-alcoholic fatty liver diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 100 publications
1
18
0
1
Order By: Relevance
“…Our findings, similar to our previous systematic reviews and meta-analyses on the importance of food sources of fructose-containing sugars on other cardiometabolic outcomes [ 8 , 11 , 124 , 125 , 139 ], suggest that the focus of dietary guidelines [ 151 ] should be on dietary patterns, recognizing the importance and complex interactions of the food matrix and the energy conditions under which foods are consumed, rather than limited to single nutrients, like total fructose-containing sugars. Our present results demonstrating the benefit of fruit on inflammation are also supported by the Global Burden of Disease Study which showed the most important contributors to the global burden of morbidity and mortality are foods we should increase intake of, include increased intake of fruit [ 152 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings, similar to our previous systematic reviews and meta-analyses on the importance of food sources of fructose-containing sugars on other cardiometabolic outcomes [ 8 , 11 , 124 , 125 , 139 ], suggest that the focus of dietary guidelines [ 151 ] should be on dietary patterns, recognizing the importance and complex interactions of the food matrix and the energy conditions under which foods are consumed, rather than limited to single nutrients, like total fructose-containing sugars. Our present results demonstrating the benefit of fruit on inflammation are also supported by the Global Burden of Disease Study which showed the most important contributors to the global burden of morbidity and mortality are foods we should increase intake of, include increased intake of fruit [ 152 ].…”
Section: Discussionsupporting
confidence: 92%
“…The lack of harm observed for SSBs alone at all levels of energy control is supported by a previous systematic review and meta-analysis including 7 trial comparisons of fructose versus glucose which showed no overall effect [ 121 ]. Previous systematic reviews and meta-analyses exploring the effect of different food sources of fructose containing sugars on cardiometabolic outcomes in controlled trials have demonstrated harm when SSBs are consumed as a source of excess calories, including on glycemic control, adiposity, blood pressure and uric acid [ 8 , 11 , 139 , 140 ]. It is possible that the lack of harm observed in the present analysis may be the result of fewer trials and those which only comprised of healthy participants free of chronic diseases and with low baseline CRP levels (median 0.4 mg/L, range 0.2–1.22 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…30 A systematic review was agree with this speculation that food source may mediate the effect of nutrients on NAFLD development. 39 The white rice pattern was characterised by high rice consumption in the present study. Chung et al also identified a similar dietary pattern, named the 'simple meal pattern', and reported no association with NAFLD risk.…”
Section: Discussionmentioning
confidence: 45%
“… 30 A systematic review was agree with this speculation that food source may mediate the effect of nutrients on NAFLD development. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Die Ergebnisse einer kürzlich veröffentlichen Meta-Analyse, die den Einfluss der Quelle der Fruktose (z. B. zuckergesüßte Getränke, Obstsaft, Süßwaren, gesüßte Milchprodukte) und des Energiegehalts auf Marker der NAFLD in 51 Studien untersuchte, weisen ebenfalls darauf hin, dass vor allem eine überschüssige Energieaufnahme aus zucker- (fruktose-) gesüßten Getränken mit dem Anstieg des Leberfetts und der ALT Aktivität im Blut einhergeht 5 . In dieser Untersuchung fand sich auch ein positiver Effekt auf den Leberfettgehalt bei einer Reduktion der Aufnahme von Fructose aus gesüßten Getränken.…”
unclassified